Appropriateness of prescribing thyroxine in primary care. (July 2015) - Cooper, Rachel; Pinkney, Jonathan; Ayling, Ruth M
Introduction: A practice hypothyroid register is part of the quality and outcomes framework. In literature, the prevalence of hypothyroidism is stated to be 2% but the prevalence, defined from quality and outcomes framework data, is 3.2% in the UK and 3.6% in Plymouth. We sought to investigate the diagnosis of hypothyroidism and reasons for prescription of thyroxine to patients on the hypothyroid register in Plymouth. Methods: A letter was sent to the 10 practices with the highest prevalence of hypothyroidism requesting a list of patients on their registers. The hospital pathology system was used to identify those with biochemically documented hypothyroidism (defined as thyroid stimulating hormone >10mU/L) For two large practices the clinical records of the remaining patients were reviewed to ascertain the reasons for prescription of thyroxine and whether it led to symptomatic improvement. Results: Seven practices responded with 1246 patients on their registers, of whom 43.6% had documented hypothyroidism. A review of notes of patients on the register, but without documented hypothyroidism, showed <25% to have an improvement in symptoms after prescription of thyroxine. Tiredness was the most common symptom prompting prescription of thyroxine. Conclusion: Of the patients on the register, only 43.6% had documented biochemical evidence of hypothyroidism and, from notes review of those without documented hypothyroidism, at least two-thirds may have been prescribed thyroxine outwith current national guidance. If this is correct, it has significant resource implications, impacts upon the workload of primary care, pharmacy and the laboratory service and may have clinical implications for patients.